2002
DOI: 10.1055/s-2002-36740
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy Surgery Outcome in Children with Focal Epilepsy due to Tuberous Sclerosis Complex

Abstract: kinsonism and dementia. Brain MRI show iron in the substantia nigra and globus pallidus, as well as a halo of T1 hyperintense signal in the substantia nigra and cerebral peduncles. Male and female patients were phenotypically similar. Conclusion: We describe the first X-lined form of NBIA, due to mutations in WDR45. The phenotypic similarity between the sexes is likely due to somatic mosaicism in surviving males. WDR45 encodes a beta-propeller protein postulated to play a role in autophagy, a novel disease mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 22 publications
4
52
0
2
Order By: Relevance
“…These include electroencephalography, PET imaging, ictal SPECT, and magnetoencephalography. 13,15,18,[33][34][35][36][37][38][39][40] Each isolated technique had variable success to correctly identify the problematic cortical tuber. However, the favored approach is to use multiple complementary imaging modalities to accurately and confidently localize the epileptogenic focus before surgical resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include electroencephalography, PET imaging, ictal SPECT, and magnetoencephalography. 13,15,18,[33][34][35][36][37][38][39][40] Each isolated technique had variable success to correctly identify the problematic cortical tuber. However, the favored approach is to use multiple complementary imaging modalities to accurately and confidently localize the epileptogenic focus before surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the favored approach is to use multiple complementary imaging modalities to accurately and confidently localize the epileptogenic focus before surgical resection. 13,15,18,[33][34][35]37,[39][40][41] When seizures can be localized to a single epileptogenic tuber, surgical resection has proved beneficial, with significant reductions in seizure frequency. 15,18,33,[35][36][37][38] Future studies with PASL could localize the epileptogenic tuber by establishing the baseline perfusion values of the cortical hamartomas and evaluating the perfusion change associated with the ictal or postictal state similar to nuclear medicine SPECT examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Over the 40 years since that report, the published literature has consistently found that traditional resective epilepsy surgery can be very successful in reducing the seizure burden in carefully selected patients with TSC who harbor a single tuber and associated epileptogenic focus. 3,5,8,18,[26][27][28]34,35,37,41,52,57,75 Patients not meeting this selection criterion for surgery were offered a palliative approach, such as corpus callosotomy. 18 A review of the TSC epilepsy surgery literature indicates that patients with a well-localized single tuber and corresponding epileptogenic zone are excellent surgical candidates, but children not fitting this profile are often excluded from operative treatment because a poor outcome was anticipated.…”
Section: Surgical Strategiesmentioning
confidence: 99%
“…Therefore, early identification of potential surgical candidates is critical for seizure control and optimal development. However, the published literature primarily contains reports on older children, 3,5,8,18,[26][27][28]34,35,37,41,52,57,75 with very few younger patients included in these series. This raises the question of whether a potential benefit is not seen because surgery is delayed beyond a potentially important developmental window.…”
Section: Neurosurg Focus / Volume 25 / September 2008mentioning
confidence: 99%
See 1 more Smart Citation